2022
DOI: 10.1111/ijfs.15666
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and antimicrobial properties of pulse proteins and their applications in gluten‐free foods and sports nutrition

Abstract: Summary Pulses are inexpensive and eco‐friendly source of biologically active proteins/peptides exhibiting antioxidative and antimicrobial properties. The antimicrobial activity of pulse proteins/peptides is ascribed to their ability to interact with components of bacterial/fungal cells or viral‐envelope, while antioxidative effects are the result of absorption/scavenging of free radicals and reactive oxygen species, which depend on amino acid composition/sequence, hydrophobicity and molecular mass and vary wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 109 publications
(160 reference statements)
0
15
0
Order By: Relevance
“…Pulses are inexpensive source of proteins, complex carbohydrates, vitamins, minerals and many health-benefitting phytochemicals ( Shevkani et al, 2022 ). The inclusion of pulses in diets is generally recommended for healthy aging, obesity prevention, diabetes management, relieving constipation and reducing the risk of chronic diseases including coronary artery diseases and some cancers ( Brennan et al, 2016 ; Shevkani and Chourasia, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pulses are inexpensive source of proteins, complex carbohydrates, vitamins, minerals and many health-benefitting phytochemicals ( Shevkani et al, 2022 ). The inclusion of pulses in diets is generally recommended for healthy aging, obesity prevention, diabetes management, relieving constipation and reducing the risk of chronic diseases including coronary artery diseases and some cancers ( Brennan et al, 2016 ; Shevkani and Chourasia, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, 10% supplementation level could be use to increase antioxidant quality without decreasing of the sensorial properties. During the last decade, the request to gluten free product has increased (Shevkani et al ., 2022). Silav‐Tuzlu & Tacer‐Caba (2021) investigated the using of chia seeds in gluten free biscuits and reported that chia seeds caused an increase in the overall acceptability and flavour scores of biscuits.…”
Section: Resultsmentioning
confidence: 99%
“…Commonly, legumes including the underutilized ones are rich in polyphenols, alkaloids, saponins, carotenoids, terpenoids, omega-3 fatty acids, flavonoids, and anthocyanins amongst others (Figure 3). These substances have varying degrees of abilities to act as antioxidants, antimicrobials, anticancer agents, anti-tumor agents, anti-inflammatory agents, and neuroprotective agents (Zheng et al, 2019;Shevkani et al, 2022;Popoola et al, 2022a). Furthermore, it has been suggested that polyphenols, alkaloids, and saponins play a vital role in protecting the plant from herbivores and pathogens by serving as defense mechanisms.…”
Section: Bioactive Components Of Underutilized Legumesmentioning
confidence: 99%